MA’ANI AL-HURUF DAN IMPLIKASINYA TERHADAP IJTIHAD - Bahri Nasution, Khairul (Al-Qadha, 2018)
In the development of Islamic law were encountered wide difference of opinion of the scholars as the fruit of the seriousness in exploring settlement of legal matters from the sourceQur'an and the Sunnah. The difference there is that is born of the understanding of the passage oflaw, the arguments of the disputed law, the validity proposition of law, there is even born rules ofthe Arabic language. Among the differences born of the rules of the Arabic language is thedifference in meaning of the letter. The letters in Arabic are the third component of the kalimatafter the word isim and fi?il. The letter is any wor that has no meaning, but if it is shared in otherwords. Huruf (letter) also divides into two, namely: mabani and Ma'ani. In Ma'ani letter, the letterdistributed to two, namely ?amil and 'athil. Ma'ani letter of understanding to be born diversemeanings to a letter that implicates to disagreements over the meanings of verses and hadith bothon the Aqeedah and Fiqh.